The Nail Penetration Behaviour of Carbon Nanotube Composite Electrodes for Energy Storage - Koliolios, Evangelos; Mills, Daniel G.; Busfield, James J. C.; Tan, Wei (Frontiers in Materials, 2021)
The crashworthiness of carbon nanotube (CNT) composites has not been extensively studied for energy storage application. Nevertheless, it is important to understand its mechanical behaviour before it is made commercially available regarding the safety concerns. This article discusses the nail penetration of electric double layer supercapacitor specimens consisting of CNT electrodes and pseudocapacitor specimens with carbon nanotube-polyaniline(CNT/PANI) electrodes for both dry and wet cells. Different behaviours are observed between the different specimens as the dry cells follow the a power law and the wet cells follow a piece-wise relationship, which is initially exponential and then becomes linear. This investigation uses the Johnson-Cook model to simulate the dry cell behaviour. The coefficients of Johnson-Cook model are calibrated from the experimental load-displacement curves. The finite element model prediction exhibits relatively good agreement with the experimental results. Also by recording the force, voltage across the supercapacitor and temperature on the surface of the supercapacitor, no temperature change or overheating was observed after short-circuit. Moreover, electrochemical testing is performed before and after the specimen penetration. The cyclic voltammetry shows the dramatic loss of capacitance, changing the cell behaviour from capacitor to resistor-like manner.